2009
DOI: 10.1088/0953-8984/21/24/245104
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations on PbO–Sb2O3–B2O3:CoO glass ceramics by means of spectroscopic and dielectric studies

Abstract: PbO-Sb(2)O(3)-B(2)O(3) glasses mixed with different concentrations of CoO (ranging from 0 to 2.0 mol%) were crystallized. The samples were characterized by x-ray diffraction, scanning electron microscopy and differential scanning calorimetric techniques. The x-ray diffraction and scanning electron microscopic studies have revealed the presence of CoSb(2)O(6), Co(2.33)Sb(0.67)O(4), Pb(5)Sb(2)O(8),Pb(3)(SbO(4))(2), PbB(4)O(7) and Co(3)O(4) crystalline phases in these samples. The DSC studies have indicated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…As a result we expect that more degree of disorder in glass ceramics containing Sb 3+ ions rather than in the glass ceramics containing Sb 5+ ions. Sb 5+ ion participates in the glass network with Sb V O 4 structural units as reported earlier [17]. As 2 O 3 is a strong network former with corner sharing AsO 3 pyramidal units [29,30].…”
Section: Discussionsupporting
confidence: 60%
“…As a result we expect that more degree of disorder in glass ceramics containing Sb 3+ ions rather than in the glass ceramics containing Sb 5+ ions. Sb 5+ ion participates in the glass network with Sb V O 4 structural units as reported earlier [17]. As 2 O 3 is a strong network former with corner sharing AsO 3 pyramidal units [29,30].…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, Sb 5+ O 4 units play a similar structural role to BO 4 units and as a result there is a possibility for the formation of linkages of the type Sb-O-B [22]. However, it may be worth mentioning here that our earlier studies on non-linear optical properties of these glasses have indicated that the presence of Sb 5+ ions is a hindrance for optical poling and for photo induced birefringence [4,5].…”
Section: Discussionmentioning
confidence: 82%
“…Antimony ions may also exist in Sb 5+ state and participate in the formation of glass network with Sb 5+ O 4 structural units that may cross-link with borate structural units in Sb 2 O 3 -B 2 O 3 glass network. Recently we have reported detailed studies on non-linear optical properties of antimony oxide based glasses crystallized with CoO and TiO 2 [4,5]. These studies have yielded quantitative information regarding optical characteristics of these glasses and also have thrown some light on the possible use of these glasses for NLO devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photo-inducing 7 ns 1064 nm Nd:YAG laser was incident on the sample at angle about 5-7 degree with respect to the surface normal. The photoinducing UV laser beam and the probing laser beams were temporary synchronized, the other details of these measurements can be found in our earlier reports [16].…”
Section: Experimental Methodsmentioning
confidence: 99%